A relação entre o ensino da educação física proposto pela BNCC e o que é ensinado de acordo com o PPP de uma escola de ensino médio - Nunes, Lucas Santos (Brasil, 2025)
This Final Course Work analyzes the guidelines of the National Common Curricular Base (BNCC) and the Pedagogical Political Project (PPP) that are broken in Physical Education classes at a high school in Manaus, based on observations made during the mandatory supervised internship. With a qualitative and descriptive approach, instruments such as direct observation, field reports and document analysis were used. The results indicate that, although the BNCC promotes inclusive, interdisciplinary and specific practices for the integral development of students, there is a lack of adequate infrastructure and materials that compromise the full implementation of these guidelines. On the other hand, the PPP contextualizes these standards to the school environment, promoting inclusion and valuing diversity, but still needs greater alignment with the BNCC. Innovative practices were identified, such as active methodologies and interdisciplinary activities, which enriched learning and promoted student autonomy. Conclude that, for Physical Education to fully fulfill its transformative role, it is essential to overcome structural challenges through investments and pedagogical planning that takes into account local realities, ensuring effective application of the BNCC and the PPP.